Removal of Discoloured Impurities from Feldspar Ores by Bulk Floatation - KILINC AKSAY, ECE (Asian Journal of Chemistry, 2010)
Feldspar ores usually contain the principal discolouring impurities of mica, titanium and iron bearing minerals, which impart colour and in turn degrade the quality of the ore. In this study, the possibility of removing mica, iron and titanium bearing mineral from feldspar ore in a single stage floatation experiment in mildly alkaline pH conditions compared to the more commonly used reverse multi-stage floatation in acidic pH conditions was investigated. For this, several collectors and their combination were tested in the single- and multistage floatation methods. This study has showed that the main impurities in the feldspar ore can be floated in an alkaline medium by bulk floatation, i.e. in one-stage, using Aero 704 collector supplied from Cytec Industries, Inc. The results of bench scale floatation tests to evaluate the performance of individual collectors and their blends will be reported along with the elaboration of the mechanism of the collector action. The parameters considered in the evaluation were grades of TiO2 and Fe2O3 in the feldspar concentrate and their removal recoveries from the feldspar ore.